Free‐Standing Metasurfaces for High‐Efficiency Transmitarrays for Controlling Terahertz Waves. Issue 3 (11th December 2015) - Liu, Shuo; Cheng, Qiang; Xu, Quan; Wang, Tian Qi; Du, Liang Liang; Luan, Kang; Xu, Yue Hong; Bao, Di; Fu, Xiao Jian; Han, Jia Guang; Zhang, Wei Li; Cui, Tie Jun
Abstract : An ultrathin free‐standing metasurface is proposed to bend the normally incident terahertz wave to an anomalous direction, or to focus plane wave to a point, with high efficiency. The flexibility and endurable nature of the proposed transmitarray make it a promising candidate for various THz applications such as time‐domain system or THz imaging devices.